2013
DOI: 10.1089/ars.2011.4491
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Nrf2-Mediated Gene Transcription by Extremely Potent Synthetic Triterpenoids Attenuate Dopaminergic Neurotoxicity in the MPTP Mouse Model of Parkinson's Disease

Abstract: Although the etiology of Parkinson's disease (PD) remains unclear, ample empirical evidence suggests that oxidative stress is a major player in the development of PD and in 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) neurotoxicity. Nuclear factor E2-related factor 2 (Nrf2) is a redox-sensitive transcription factor that upregulates a battery of antioxidant response element (ARE)-driven antioxidative and cytoprotective genes that defend against oxidative stress. Aims: We evaluated whether the strategy of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
117
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(118 citation statements)
references
References 53 publications
1
117
0
Order By: Relevance
“…The Nrf-2 signaling cascade is a promising therapeutic pathway via transcriptional modulation of both inflammation and oxidative stress, and it has generated increasing clinical interest in using Nrf-2 activators in inflammatory diseases (32). A number of drugs that activate the Nrf-2 system are already in clinical use, including the fumaric acid ester DMF (57).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Nrf-2 signaling cascade is a promising therapeutic pathway via transcriptional modulation of both inflammation and oxidative stress, and it has generated increasing clinical interest in using Nrf-2 activators in inflammatory diseases (32). A number of drugs that activate the Nrf-2 system are already in clinical use, including the fumaric acid ester DMF (57).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Nrf-2 activation was observed in humans in settings of chronic diseases such as PD (30,32,37), Alzheimer's disease (14), and amyotrophic lateral sclerosis (52). Brennan et al showed that DMF, by acting as an electrophile, modulates specific KEAP1 cysteine residues and exerts more robust allosteric conformational changes-leading to a diminished KEAP1-dependent degradation of Nrf-2 (10).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The neuroprotective effect of these TP against MPTP neurotoxicity was dependent on NRF2, since treatment with TP in NRF2 knockout mice Diagram of the molecular events triggered by α-synuclein and the protective way of action of DMF through NRF2 activation. DMF through NRF2 is able to modulate protein aggregation (modifying proteasome and autophagy), oxidative stress (increasing the expression of antioxidant enzymes) and neuroinflammation (increasing anti-inflammatory markers and reducing pro-inflammatory cytokines) failed to block against MPTP neurotoxicity and induce NRF2-dependent cytoprotective genes [102].…”
Section: Pharmacologic Targeting Of Nrf2 As a Disease Modifiying Thermentioning
confidence: 99%
“…Moreover, an impressive number of disease-specific proteins interact with mitochondria. Thus, therapies targeting basic mitochondrial processes, such as energy metabolism or free-radical generation hold some promise (Kaidery et al, 2013).…”
Section: Tissuementioning
confidence: 99%